Impact of Endogam Marriage on Government of Tenganan Pegringsingan Traditional Village, Bali - Ni Nyoman Putri Nursanti (Budapest International Research and Critics University, 2022)
This article aims to describe an endogamous marriage that has an impact on the existence of the customary village government system. The research method used to search for data from this paper is document study, observation and interviews with traditional leaders in the traditional village of Tenganan Pegringsingan, Bali. The research data, both secondary and primary, were presented descriptively which were previously analyzed qualitatively. The results of the study show that the existence of the marriage system and government system in the Tenganan Pegringsingan traditional village is like a currency, one side of the marriage system while the other side is the traditional village government system. The relationship between the two institutions is not just an ordinary relationship, but as a conditional relationship, meaning that if you want to get a share of 'tika' as a monthly villager's income (such as salary), it is necessary to fill in the traditional village government structure through endogamous marriage. According to Koentjaraningrat's view, the strength of this existence will undergo a very long change. This is because individuals since childhood have been infused with cultural values that live in society so that these conceptions have long been rooted in the realm of their souls. That is why these cultural values are difficult to replace with other cultural values in a short time.